P83-F Reinnervation in masseteric nerve supercharge bypass in primary reconstruction of facial nerve. Issue 7 (July 2019) - Brusakova, Stepanka; Vachata, Petr; Lodin, Jan; Sames, Martin
Abstract : Background: Facial paralysis is a severe disease. A wide variety of surgical procedures to facial nerve reconstruction are available. We demonstrate reinnervation after infratemporal end-to-end anastomosis following nerve rerouting and concomitant masseteric nerve transfer to the side of facial nerve trunk. Masseteric nerve transfer seems to have strong reinnervation potential. Material and methods: Patient presented with complete unilateral facial nerve palsy on the left side with the absence of clinical movement and no signs of reinnervation on needle electromyography. The ipsilateral masseteric muscle nerve electromyography and function was without deterioration. After reconstruction, the patient was regularly clinically and electromyographically evaluated throughout a three-month postoperative period. Results: The first control showed no electromyographic signs of reinnervation. Reinnervation in both upper and lower part of face after six months was observed with richer and more mature voluntary activity in orbicularis oris muscle. Synkinetic activity with biting was observed. Three months later, the patient achieved facial symmetry at rest and palpebral closing significantly improved with a residual 3 mm gap. Electrophysiological evaluation 12 months after surgery showed improved reinnervation of mimic muscles during biting and relaxation of chewing muscles at both donor nerve sites, as well as clinical recovery of the capacity to spontaneously blink, complete eyelid closure and initials signs of smile. Conclusions: Double innervation of muscular transfer allows additional target muscle reinnervation, with simultaneous preservation of donor nerve function. Electromyography needle evaluation 12 months after surgery declares independent reinnervation through both donors.